Polarographic Determination of Topiramate in Some Pharmaceuticals - Mandil, H.; Sakur, A.A.; Alulu, S. (Asian Journal of Chemistry, 2010)
A differential pulse polarographic analysis has been used for the determination of topiramate in aqueous medium, which contains a phosphate buffer 0.01 M at pH = 9.50 using dropping mercury electrode (DME), static mercury drop electrode (SMDE) and hanging mercury drop electrode (HMDE). Reduction peak for topiramate was occurred in potential (Ep) range from 74 to 77 mV. The peak current (Ip) is propor-tional to the concentration of topiramate over the ranges 1.36-19.04 μg mL-1 using DME and 4.08-27.2 μg mL-1 using SMDE and HMDE. The limit of quantitation was 1.36 μg mL-1 with a relative standard deviation (RSD) of 3.8 % using DME and 4.08 μg mL-1 with a relative standard deviation of 2.8 % and 4.5 % using HMDE and SMDE, respectively. Therefore, this polarographic method can be applied successfully for the determination of topiramate. The proposed method is applied to the direct determination of topiramate in some pharmaceutical formulations (tablets), by differential pulse polarography (DPP). The results obtained can be observed that, the difference between the expected and the results found values by this method are less than 1.36 μg mL-1 with the RSD is less than ± 3.8 %.